Does combined antegrade and selective coronary graft cardioplegia reduce conduction defects in right coronary artery occluded patients? - Uğur, Oğuz; Kalender, Mehmet; Gökmengil, Hayat; Bingöl, Hakan (Journal of Surgery and Medicine, 2018)
Aim: Post coronary artery bypass grafting (CABG) procedure conduction disturbances may appear due to many reasons. In this particular study we compared postoperative cardiac rhythm disturbances in right coronary artery (RCA) occluded patients, which cardioplegia disturbed with antegrade aortic and continuous retrograde way versus antegrade plus continue right coronary graft. Methods: A total of 104 patients with right coronary artery occlusion who underwent isolated CABG procedure between 2011 and 2017 were included. The number of female patients was 43 (41.4%). Left bundle branch, left branch hemi block, and left branch hemi block and 3rd degree atrioventricular (AV) blocks were evaluated in the early postoperative period. Results: The mean age of patients was 55.54±4.42 years (range 46-65 years). There was no statistical difference among groups according to preoperative and intraoperative demographics. Postoperative rhythm disturbances were higher in Group 1 but there was no statistical difference. (Group 1: 9 patients and Group 2: 4 patients. p=0.378). Hospital stay and intensive care unit (ICU) stay had statistically significant difference among groups (Group 1 mean hospital stay was 7.40±1.31 days and Group 2 had mean 6.53±1.19 days p=0.026 and Group 1 mean ICU stay was days 2.20±0.67 and Group 2 had mean 1.87±0.72 days p=0.021). Conclusion: We believe that continuous RCA-selective cardioplegia administration in addition to antegrade cardioplegia may be more successful in terms of prevention of postoperative rhythm disturbances in postoperative CABG applied patients.